Fraters' Learning Approach for Understanding English Philosophical Texts Through the MOOC - Seva, Kristining (UIN Sunan Gunung Djati Bandung, 2024)
This study examines the impact of the Frater learning approach through Massive Open Online Courses (MOOCs) in enhancing the reading comprehension skills of philosophy students tackling English-language philosophical texts. By integrating pre-tests, post-tests, and qualitative feedback, the research highlights how MOOCs address challenges in understanding dense and complex philosophical material. The findings reveal a significant 11% improvement in reading comprehension after MOOC participation, emphasizing its effectiveness in breaking down intricate concepts into manageable components. Key elements contributing to this success include segmented video content, which facilitates focused learning, and interactive assessments that reinforce comprehension in real time. This research underscores the potential of the MOOC-based Frater approach as an innovative solution for bridging language and content barriers in the study of philosophy.